The Curvilinear Relationship Between Dissatisfaction With the Status Quo and Innovative Behavior - Wang, Siyuan (Frontiers in Psychology, 2022)
To enhance the understanding the relationship between dissatisfaction with the status quo and innovation, this study proposed that dissatisfaction with the status quo has a curvilinear relationship with innovative behavior and job security moderates the association between these two variables. An investigation based on 214 employees from Chinese companies was conducted. The results indicated that dissatisfaction with the status quo has an inverted U-shaped relationship with idea dissemination and idea implementation, and job security moderates the inverted U-shaped relationship. Specifically, for individuals with a low job security, the curvilinear relationship is stronger, whereas for individuals with a high job security, the slope of the curve becomes nearly flat, thus losing the inverted-U effect. Theoretical and practical implications are discussed, and directions for future research are outlined.